Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus Terhadap Kesejahteraan Masyarakat Melalui Pertumbuhan Ekonomi Dalam Perspektif Ekonomi Islam di Kabupaten Langkat - Risca Yunia Lestari; Muhammad Ridwan; Maryam Batubara (ITB AAS INDONESIA Surakarta, 2023)
The welfare of the community is a condition that many parties want to achieve, one of which is the local government who wants to prosper regional autonomy in various aspects. People who can meet all their needs, facilitate access in many ways, get proper facilities, and others are the goals and responsibilities of the blood government. The purpose of this study was to determine the extent of the influence of the dependent variable on the independent variable through intervening variables that describe what conditions have an influence or not on the welfare of the people of Langkat Regency. This research method uses a quantitative approach that uses path analysis and uses SPSS (Statistical Package for the Social Sciences) version 25 for window program assistance. This study uses secondary data within the last 5 (five) years. The results show that simultaneously (overall) Regional Original Income (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) have an effect on economic growth, meanwhile Regional Original Income (PAD) and economic growth have no effect on welfare. community, then the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) have a direct effect on the welfare of the community, and the last one is Regional Original Revenue (PAD), the General Allocation Fund (DAU), and the Special Allocation Fund (DAK) have no indirect effect. directly to the welfare of society. Economic growth related to welfare can be obtained only by piety to Allah Subahana Wataala and also speaking honestly and truthfully. In an Islamic Economic Perspective, people are encouraged to pay attention to the welfare of future generations.